The Phoenix Biennial. - The Phoenix Biennial, 1985 (Phoenix : Phoenix Art Museum, 1985)
Marks, Pamela ; Weller, Susan ; Klotz-Reilly, Suzanne ; Mundwiler, Linda ; Tilger, Susanne ; Forsman, Chuck ; Cowlin, James ; Braendle, Charles ; Golden, Judith ; Putzar, Edward ; Peck, Mary ; Kaida, Tamarra ; West, Gregory ; Umeda, Kenji ; Borcherdt, Fred ; McGrew, Fox Joy ; Lowe, Ed ; Roots, Garrison ; Asay, Roger ; Davis, Rebecca
The Phoenix Biennial, Phoenix Art Museum, Phoenix, July 6 to August 4, 1985
boek